Fenomena "Rent Seeking" di Daerah: Kasus Tata Niaga Kayu Cendana - Syarif Hidayat (Jurnal Ilmu Sosial dan Ilmu Politik, 2001)
Local elite, as the case of handling of sadle-wood business shows, are more prone to rent seeking practice. The failure to draw a clear boundary between public and private interest has on the one hand allow them to optimize their personal gain through rule of the game they have set up and implemented.